The modernity-postmodernity debate in Peru: Reflections on the text "Goodbye to modern discourse in Peru" by José Ignacio López Soria - Carranza Elguera, Víctor Humberto (2007)
After establishing the impact of the postmodern proposal on contemporary consciousness, the author focuses on the matrices of the debate generated in Peru (the regenerative, traditional and postmodern options) to, with these instruments, discuss the dissociation between the abstract and the deductive ones of modernity that would characterize the Peruvian problematic. Finally, he discusses López Soria's approaches, the autonomization of discourse, the economic dimension, the absence of alternatives, and the urgency of regenerating politics.